High intensity events and post-match fatigue in football - Wiig, H.; Luteberget, L.; Raastad, T.; Spencer, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Football matches produce post-match fatigue and time until full recovery may take several days (Nedelec et al., 2012). The slow recovery, probably related to muscle damage, has been associated to the high intensity activities during the match (e.g. Russel et al., 2016). However, the role of accelerations and decelerations in this relationship is not well understood. Therefore, the aim of this study was to investigate high intensity events (HIE) in football matches using Inertial Measurements Units (IMU) and its interaction on postmatch fatigue and indicators of muscle damage. Methods: Six Norwegian 2. division teams (n=81) were recruited to play three matches. IMUs (Catapult Optimeye S5, Australia) with 100Hz accelerometer, magnetometer, and gyroscope were worn in a vest placed on the upper back. HIE, the sum of accelerations, decelerations, change of directions efforts and jumps (>2.5 m·s-1), were quantified and expressed as counts per minute. Players were divided into keepers (KE;n=6), central defenders (CD;n=13), full backs (FB;n=13), central midfielders (CM;n=23), wide midfielders (WM;n=16) and attackers (AT;n=10). Countermovement jumps (CMJ;n=56) and Creatine Kinase (CK;n=35) were measured 1 hour pre and 1, 24, 48 and 72 hours` post-match (KE excluded). Differences were deemed likely (L), very likely (VL) and most likely (ML) when there was a likelihood of > 75%, 95% and 99% of the difference exceeding an effect size of 0.2 respectively. The interaction of HIE on fatigue was investigated using mixed model analysis (fixed effects: time·HIE and random effects: subjects + teams). Results: On average, HIE occurred 2.1±0.7 times per minute (mean±SD) including 0.3±0.1 accelerations, 0.5±0.2 decelerations, 1.3±0.5 changes of direction and 0.05±0.03 jumps and were position depended: WM (2.5±0.5), CM (2.4±0.5), AT (2.2±0.5), FB (2.0±0.6), CD (1.8±0.5) and KE (0.8±0.2). Differences ranged from L to VL. The percent changes from pre to +1h, +24h, +48, and +72h were -6.6 (VL), -6.2 (VL), -6.6 (VL) and -4.7 (L) for CMJ height and 69 (ML), 112 (ML), 42 (L), 4.1 (unclear) for CK respectively. Lastly, our model showed no interaction of HIE on neither CMJ nor CK for any of the time points. Discussion: HIE were found to be position depended and thus, players from different positions are loaded differently in matches. The match load produced neuromuscular fatigue lasting for 72 hours. However, a direct interaction of total HIE on fatigue or muscle damage was missing, suggesting that the match load and fatigue relationship is more complex. Player fitness, pre-match fatigue, and match effort could possibly interact in this relationship. ABSTRACT FROM AUTHOR